Comparative Study of Polygamy Marriage Regulations in Turkey, Russia, and Jordan: a Priority Fiqh Perspective - Rahmatullah, Prayudi; As-Suvi, Ahmad Qiram; Ainur Rofiq, Mahbub; Mahsyar , Nun Maziyyah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2023)
Polygamy marriage has been an ongoing worldwide debate. The regulation of polygamy marriage in Turkey, Russia, and Jordan faces challenges in addressing the complexity of social issues. This article aims to explore and evaluate the polygamy marriage regulation in these three countries, from a social and fiqh (Islamic jurisprudence) priority perspective. The fiqh priority perspective emphasizes the common good and prioritizes long-term benefits. The article outlines diverse views on polygamy, including arguments supporting polygamy as a solution to specific social problems, as well as the complex social implications of polygamous practices. Furthermore, a comparative study of polygamous regulation in Turkey, Russia, and Jordan reveals differences in approaches to governing polygamy and how it affects societies within different social, cultural, and religious contexts. Through an analysis of social perspectives and fiqh priority, this article provides a deeper understanding of the regulation of polygamous marriage in Turkey, Russia, and Jordan, along with considerations that need to be taken into account in addressing this issue.